Market Diffusion of Extended Cycle Hormonal Contraceptives - Megen Leeds Schumacher, Pharm.D; Ashley Cetola Pettia, Pharm.D; Albert I Wertheimer, PhD, MBA, Professor (University of Minnesota Libraries Publishing, 2012)
Background: Extended cycle hormonal contraceptives (e.g. Seasonale, Seasonique) when introduced in 2003 were considered a very novel approach to contraception. The idea of manipulating the menstrual cycle so that women would experience just four menstruations a year was radical and was assumed to be responsible for the slow acceptance rate among the general public.Objective: This report analyzes two different aspects of the acceptance of this unique idea in the population. The first was the level of usage of extended cycle hormonal contraceptives in the general population, which was measured by a review of sales figures over time in the United States. The second was an examination of market diffusion as it relates to consumer perceptions regarding the characteristics of these products.Methods: To determine the degree of usage of extended cycle hormonal contraceptives the yearly sales, in terms of units sold, were compared with that of other leading methods of hormonal contraception. Along with the data, survey answers were obtained from 65 women who volunteered to participate in the study. Participants were selected randomly to represent the target population to assess the level of awareness about the benefits, risks, and any other concerns regarding the use of extended cycle hormonal contraceptives.Results: The yearly sales data of units sold showed a definitive increase in the sales of extended cycle hormonal contraceptives since their release on the market. The survey results showed an overwhelming awareness in the study population about the extended regimen. However, only about half of the women in the survey group were aware of its benefits. The main concern reported was the perceived significant side effect profile.Conclusion: Though awareness about the extended cycle hormonal contraception regimen was widespread, the survey population was not well informed about the advantages and the disadvantages regarding the degree of severity of side effects. To address these knowledge deficits, these aspects should be the focus when distributing information about extended cycle hormonal contraceptive regimens. This may boost the use of a potentially advantageous contraceptive regimen by a population who would derive benefit from its usage.